Solomon, R.C. (2007). Ética emocional. Una teoría de los sentimiento. Barcelona: Paidós. ISBN: 978-84-493-2049-1. Número de páginas: 388. - Palma Muñoz, José Manuel; Universidad de Granada (2009)
null